Possible impacts of the European Green Deal on Turkey's logistics industry - Fatih Cura; Sercan Demir (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: The concept of the Green Deal is one of the important roadmaps adopted to build a more livable world against the climate crisis and make the current system cleaner and more sustainable. Businesses in the EU are subject to sustainability rules required by the Green Deal. Since Turkey is a signatory power to the agreement, the Turkish companies are also hinged on to the Green Deal. The logistics sector emerges as one of the priority areas on this matter. In this sense, Turkey has also prepared a 'Green Deal Action Plan' to adapt to the new situation. In this study, Turkey's competencies in international logistics will be evaluated, and the compatibility of the planned actions with the green deal process will be discussed. Methodology: This research is conducted to review literature from recent journals, governments reports, and the World Bank's logistics performance index (LPI) to draw out secondary data that helped analyze the drivers of the EU's green deal practices and the challenges faced by Turkey's logistics industry in implementing them. Findings: Turkey's competencies in international logistics and action plans to comply with the Green Deal are examined. Originality: This study is novel in examining Turkey's logistics compatibility with EU's Green Deal rules.
urn:nbn:de:gbv:830-882.0200700; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Sustainability; Supply Chain Management; Logistics